Bartter syndrome type III with glomerular dysplasia and chronic kidney disease: A case report - Liu, Jingqi; Zhang, Yudi; Wu, Xiaochuan; Li, Yongzhen (Frontiers in Pediatrics, 2023)
Background Bartter syndrome (BS) type III is a rare autosomal recessive genetic disease. Its clinical features are polyuria, hypokalemia, hypochloremia, metabolic alkalosis, and hyperreninaemia. A few BS type III can be complicated with chronic kidney disease. Case presentation We report a 14-year-old boy with Bartter syndrome caused by a c.1792C > T (p.Q598*) mutation in the CLCNKB gene. He was a no deafness and full-term baby, and he had renal dysplasia and chronic kidney disease (CKD). In addition, we summarize all cases of BS type III complicated with CKD. Conclusions We report a case of Bartter syndrome complicated by chronic kidney disease caused by a new mutation of CLCNKB. As we all know, BS type IV is usually combined with chronic kidney disease, and BS type III can also integrate with CKD. We don't find BS type III with glomerular dysplasia in the literature. So renal damage in BS type III is not only FSGS; clinicians must also be aware of glomerular dysplasia.